Single-Tablet Regimens for the Treatment of HIV-1 Infection. (April 2017) - Sebaaly, Jamielynn C.; Kelley, Denise
Objective: To review the pharmacokinetics, safety, drug-drug interactions, and advantages and disadvantages of currently available single-tablet regimens (STRs) for HIV-1 infection.Data Sources: A search using PubMed was conducted (up to September 2016) using the following keywords: single tablet regimen AND HIV . Additionally, a PubMed search was conducted for each individual STR using the generic names of the agents. Articles were evaluated for content, and additional references were identified from a review of literature citations.Study Selection and Data Extraction: Studies included were predominantly phase III clinical trials with the exception of tenofovir alafenamide because phase I and phase II trials were also relevant for this new antiretroviral agent.Data Synthesis: Six STRs are currently available for the treatment of HIV-1. Each agent has unique pharmacokinetic, safety, and drug-drug interaction profiles that result in distinct advantages and disadvantages. Three of these agents are first-line recommended therapies per national guidelines because of high virological efficacy and tolerability.Conclusions: STRs have significantly advanced HIV management by minimizing pill burden and improving patient compliance. It is important to consider the nuances of each STR in regard to renal and hepatic function, drug interactions, and tolerability, to ensure safe and effective use.